Des fromages en friches. Le difficile renouveau de la production fromagère dans une vallée post-industrielle ariégeoise - Tristan Fournier; Olivier Lepiller; Guillaume Simonet (Revue de Géographie Alpine)
Throughout the 20th century, the development of the Vicdessos valley (department of Ariège, French Pyrenees) was oriented almost exclusively towards the aluminum industry, leading to the decline and then total disappearance of local cheese production. Once renowned, Auzat cheese, made from sheep and then cow's milk, was an important resource in the local economy until the middle of the 20th century. Based on documentary research, interviews and ethnographic observations, this article traces the social biography of this cheese since the middle of the 19th century. It analyzes the conditions of the decline of its production and the blurring of its memory. While, for the last twenty years, this post-industrial valley has turned towards the development of tourism, the article provides an understanding of the constraints that have prevented any renewal of cheese production until recently. Indeed, since the end of the 2010s, several initiatives have emerged, without the link with the valley's cheese-making past being cultivated for the moment. These initiatives show the new favorable conditions, but also the persistent obstacles, to the relocation of food circuits in this post-industrial rural territory.